1970
DOI: 10.3329/jard.v4i1.784
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Credit on MV Boro Rice Cultivation in Bangladesh

Abstract: An investigation was conducted at Mithapukur and Razarhat upazila under Rangpur and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Also, farmers had to visit the respective branch of the bank several times for getting their loan which made them incur a mentionable amount of cost for transportation, food as well as the opportunity cost of mandays for time passes to approve the loan. It is to be mentioned that, Miah et al (2006) also listed the above-mentioned items of costs for obtaining agricultural credit from Grameen Bank (GB) as well as RAKUB.…”
Section: Cost Of Creditmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, farmers had to visit the respective branch of the bank several times for getting their loan which made them incur a mentionable amount of cost for transportation, food as well as the opportunity cost of mandays for time passes to approve the loan. It is to be mentioned that, Miah et al (2006) also listed the above-mentioned items of costs for obtaining agricultural credit from Grameen Bank (GB) as well as RAKUB.…”
Section: Cost Of Creditmentioning
confidence: 99%
“…Therefore, when the loan is advanced to the farmers, they use it according to their priority of needs. On the other hand, there are some unwanted costs involved in obtaining agricultural credit (Miah et al, 2006). Therefore, it is needed to know how much is the cost for the borrowers to obtain the credit, how it is being used, and what is the impact of those credits in Boro cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…Marginal Value Productivities of the inputs are computed from the results of estimated coefficients or elasticities of the farms' production function. According to Miah et al (2006) and Tambo and Gbemu (2010), for farmers to use resources efficiently, such resources must be used until MVP is equal to MFC under perfect competition. Therefore, the resource use efficiency parameter is calculated as:…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…They suggested for improvement in land, labour, training, and easy capital access. Miah et al (2006) explored the resource use efficiency of credit users and non-credit users in modern variety of boro rice production. They showed that both types of farmers did not use inputs efficiently.…”
Section: Introductionmentioning
confidence: 99%